2007
DOI: 10.1017/s002531540705463x
|View full text |Cite
|
Sign up to set email alerts
|

Grey seal diet at the southern limit of its European distribution: combining dietary analyses and fatty acid profiles

Abstract: The north-east Atlantic grey seal, Halichoerus grypus, is widely distributed along the European coastline from northern Russia to France, with the core population centred around Scotland. To date, very little is known of the diet of the species at the southern margin of the species range. However, because grey seal numbers have been increasing over the last few decades in France, the issue of their potential interactions with coastal fisheries is frequently raised. The diet of grey seal in the Molène Archipela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 22 publications
3
31
0
Order By: Relevance
“…Therefore, while this study provides a good indication of which species are the most important contributors to the seals diet in terms of biomass, it is not a true reflection of the overall diet of grey seals in this region. This study has revealed that grey seals using the Great Blasket Island in southwest Ireland are generalist feeders, consistent with studies in other parts of the species' range , Beck et al 2007, Ridoux et al 2007. Previous dietary studies conducted in Ireland in the 1990s indicated that grey seals displayed a wide range of prey preferences, feeding predominantly on demersal species, sand eels, ling and cephalopods (Cronin et al 2010 and references therein).…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, while this study provides a good indication of which species are the most important contributors to the seals diet in terms of biomass, it is not a true reflection of the overall diet of grey seals in this region. This study has revealed that grey seals using the Great Blasket Island in southwest Ireland are generalist feeders, consistent with studies in other parts of the species' range , Beck et al 2007, Ridoux et al 2007. Previous dietary studies conducted in Ireland in the 1990s indicated that grey seals displayed a wide range of prey preferences, feeding predominantly on demersal species, sand eels, ling and cephalopods (Cronin et al 2010 and references therein).…”
Section: Discussionsupporting
confidence: 86%
“…Marine top-predator diets can be estimated using different approaches (for a recent review, see Bowen & Iverson 2013). Long-term analyses are based on the determination of stable carbon and nitrogen isotopes or on fatty acid analysis in the predator tissues (Iverson et al 1997;Das et al 2003;Iverson et al 2004;Ridoux et al 2007;Mèndez-Fernandez et al 2010). These methods integrate the diet of the predators over weeks or months and can provide good estimates of food webs and relationships at high trophic levels.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…These methods integrate the diet of the predators over weeks or months and can provide good estimates of food webs and relationships at high trophic levels. Information on the last few meals can be obtained by direct observation of feeding, stomach content analysis and prey hard part identification in the predator's stomachs and faeces (Bowen & Harrison 1994;Walker et al 1998;Santos & Pierce 2003;Santos et al 2004;De Pierrepont et al 2005;Ridoux et al 2007). In the stomach contents and faeces, fish and cephalopod species are deduced from the identification of otoliths and beaks, respectively, using reference material (Clarke 1986;Härkönen 1986).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…In recent years, an increasing number of studies have used fatty acid (FA) signature analysis of blubber in seals to examine foraging ecology and diet (Käkelä 1996, Käkelä & Hyvärinen 1998, Walton & Pomeroy 2003, Iverson et al 2004, Arnould et al 2005, Budge et al 2006, Smith & Worthy 2006, Beck et al 2007, Ridoux et al 2007). The underlying principle of FA signature analysis is that the chemical structure of many FAs is not altered as they pass through food webs; therefore, the FA composition in the blubber of a seal is strongly influenced by the FA composition of the diet of the seal.…”
Section: Introductionmentioning
confidence: 99%